Contamination of contact lens storage cases by Acanthamoeba and bacteria. Issue 3 (March 1990) - Larkin, D F; Kilvington, S; Easty, D L
Abstract : In order to identify possible risk factors for microbial keratitis the storage cases for contact lenses of 102 asymptomatic lens wearers were tested for contamination by bacteria and free-living amoebae. Of this group 43 had significant counts of viable bacteria and only 40 had negligible counts. Seven had contamination by acanthamoebae, of whom six also had significant bacterial counts. These results were categorised according to the type of contact lens worn and the lens disinfection method. The high rates of contamination by apathogenic and pathogenic organisms, in particular Acanthamoeba, and the probable support by contaminating bacteria of Acanthamoeba, are discussed.